Utilization of silane functionalized carbon nanotubes‐silica hybrids as novel reinforcing fillers for solution styrene butadiene rubber. Issue 5 (2nd April 2013) - Wang, Jingyi; Jia, Hongbing; Ding, Lifeng; Zhu, Lijuan; Dai, Xiu; Fei, Xiang; Li, Feng; Gong, Xuedong
Abstract Carbon nanotubes‐silica (CNTs‐SiO2) nanohybrid filler was fabricated by coating inorganic silica on multi‐wall CNTs through a sol–gel process. The CNTs‐SiO2 nanohybrids were then functionalized by 3‐methacryloxypropyltrimethoxysilane (3‐MPTS) followed by compounding to solution styrene butadiene rubber (S‐SBR) through mechanical mixing. The Fourier‐transform infrared spectroscopy showed that the CNTs were coated by inorganic SiO2, and grafted with 3‐MPTS successfully. The functionalized CNTs‐SiO2 nanohybrids had a rough surface as revealed by transmission electron microscope images. After hybridization and grafting, the functionalized CNTs‐SiO2 nanohybrids still maintained the crystal structure of CNTs, which was determined by X‐ray diffraction and Raman spectrum. The addition of nanohybrids accelerated the vulcanization process and improved the crosslinking degree of vulcanizates. With adding 10 phr (parts per hundred of rubber) functionalized CNTs‐SiO2, the mechanical properties of S‐SBR vulcanizates were improved significantly. The tensile moduli at 100% elongation (M100) and tensile strength had 54% and 28% increase, respectively. The incorporation of functionalized CNTs‐SiO2 nanohybrids also largely enhanced the storage modulus, and slightly increased the thermal conductivity of vulcanizates. POLYM. COMPOS., 00:000–000, 2013. © 2013 Society of Plastics Engineers POLYM. COMPOS., 2013. © 2013 Society of Plastics Engineers